Stripe distributions of graphene-coated Cu foils and their effects on the reduction of graphene wrinkles. Issue 117 (10th November 2015) - Zhang, Haoran; Zhang, Yanhui; Wang, Bin; Chen, Zhiying; Zhang, Yaqian; Sui, Yanping; Yu, Guanghui; Jin, Zhi; Liu, Xinyu
Abstract : The wrinkle distribution of graphene domain was obtained as trenches after hydrogen etching. Parallel stripes on graphene domains are always perpendicular to these trenches, suggesting the suppressed wrinkle formation along the stripes' direction. Abstract : Hexagonal single-crystal domains of graphene were analyzed and the wrinkle distribution was obtained using thermal hydrogen etching. We observe parallel stripes on some single-crystal domains and these stripes are associated with graphene wrinkles. The etched trenches in graphene are always perpendicular to the stripes, thereby suggesting the suppressed formation of wrinkles along the stripe direction. Results indicate that the stripes help release the internal stress of graphene to reduce its wrinkle density. Furthermore, these stripes are due to Cu surface reconstruction and relate to two main factors, namely, the distribution of Cu grains and the cooling rate after graphene growth. Continuous graphene films which are synthesized by slow cooling exhibit high stripe area coverage and low sheet resistance because of the low wrinkle density.